Acceptance of Digital Financial Applications by Students: A Qualitative Study Using the Technology Acceptance Model Approach - Paramitha, Dyah Ayu; Zulistiani, Zulistiani; Puspita, Erna (Universitas Muhammadiyah Sorong, 2026)
The purpose of this study is to delve deeper into the acceptance of financial application technology based on the technology acceptance model theory (TAM) by students who have taken investment management courses, with indicators of perceived usefulness (PU), perceived ease of use (PEU), attitude toward use (ATU), and behavioral intention (BI). This study employed a qualitative approach with thematic analysis tailored to the indicator themes. Data for this study were obtained from an open-ended questionnaire completed by 33 student respondents. The results indicate that students considered digital financial applications helpful in recording expenses, budgeting, and supporting their investment learning. Perceived usefulness and ease of use shaped positive attitudes and intentions to use the applications continuously. However, several concerns arose, including cost, data privacy, connection stability, and the complexity of certain features. This study suggests that there are lessons to be learned in the use of digital financial applications at the higher education level and also provides implications for future learning development and application design.